Media and Methods in Improving Elementary School Class 1 Speaking - Pradita, Hafidz; Anggraeni, Rahmi Adiffa Sefiana; Tristanti, Mella Tia; Nindiasari, Maharani Dwi Wahyu; Sakti, Bayu Purbha (Mauve Journal De Leardu, 2025)
Talking skills are a essential skill that need to be evolved from an early age, in particular on the primary school level, as they play a critical position within the conversation and studying system. this text examines the use of storytelling methods combined with hand puppet media and audio-visuals as a approach to enhance the speakme competencies of primary school students. thru a story qualitative technique and literature evaluation, this text shares that the storytelling approach encourages newbies to specific thoughts coherently and expressively, whilst the usage of hand puppet media can create a amusing getting to know environment and entice pupil hobby. in the meantime, audio-visual media which includes tale videos or animations provide actual examples of pronunciation, intonation, and the realization of self-expression. The mixture of these 3 proves to be powerful in shaping self-self as surance, enriching vocabulary, and growing energetic scholar participation in speakme sports. by using the use of this, the usage of suitable techniques and media can notably aid the development of students' talking skills in basic faculty.